2012
DOI: 10.3892/ol.2012.830
|View full text |Cite
|
Sign up to set email alerts
|

Increased numbers of gastric-infiltrating mast cells and regulatory T cells are associated with tumor stage in gastric adenocarcinoma patients

Abstract: Abstract. Mast cells (MCs) and regulatory T cells (Tregs)are the important components of the inflammatory infiltrating leukocytes in most malignant tumors. Our study was designed to investigate the infiltrating correlation between MCs and Tregs and clarify their prognostic significance in gastric cancer (GC). A total of 60 fresh GC tissues were collected and tumor-infiltrating leukocytes were isolated by gradient centrifugation. Tryptase and Foxp3 were used as markers for MCs and Tregs, respectively. The expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…Indeed, higher regulatory T cells have been observed in breast cancer, especially in the stage IV cancer patients that were associated with lower immune function [48]. The results of the other studies have also demonstrated an association between the increased number of intratumoral accumulation of Tregs and tumor stages which are in consistence with our findings [49,50].…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, higher regulatory T cells have been observed in breast cancer, especially in the stage IV cancer patients that were associated with lower immune function [48]. The results of the other studies have also demonstrated an association between the increased number of intratumoral accumulation of Tregs and tumor stages which are in consistence with our findings [49,50].…”
Section: Discussionsupporting
confidence: 88%
“…A large body of evidence supports the central role of angiogenesis in GC development and progression but few data regarding the role of MCs in GC angiogenesis have been published [34,35,36]. In particular, in a study performed by Mukherjee et al [37], the authors studied MCs density in tissue from patients with gastric ulcers and in tissue from GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results have several implications. First, the infiltration of mast cells into patient's skin tissues may be correlated with the increase of the number of Treg cells, as shown by the correlation of increased numbers of gastric‐infiltrated mast cells with number of Treg cells in patients with gastric cancer . We speculate that one of ways in which mast cells affect the Treg cells is their secretion of TGF‐β, which may induce FOXP3 + ‐Treg cells.…”
Section: Discussionmentioning
confidence: 93%